2021
DOI: 10.3390/ijms222011206
|View full text |Cite
|
Sign up to set email alerts
|

Parathyroid Tumors: Molecular Signatures

Abstract: Parathyroid tumors are rare endocrine neoplasms affecting 0.1–0.3% of the general population, including benign parathyroid adenomas (PAs; about 98% of cases), intermediate atypical parathyroid adenomas (aPAs; 1.2–1.3% of cases) and malignant metastatic parathyroid carcinomas (PCs; less than 1% of cases). These tumors are characterized by a variable spectrum of clinical phenotypes and an elevated cellular, histological and molecular heterogeneity that make it difficult to pre-operatively distinguish PAs, aPAs a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 66 publications
4
19
0
Order By: Relevance
“…Several genes have been identified in the pathogenesis of sporadic PA. The majority of PA are characterized by mutations in the MEN1 tumor suppressor gene located on chromosome 11q which is identified in 25% to 40% of cases 16,18,74,83 . MEN1 gene alterations are characterized predominantly by loss of heterozygosity with biallelic inactivation.…”
Section: Genetics Of Parathyroid Neoplasiamentioning
confidence: 99%
See 2 more Smart Citations
“…Several genes have been identified in the pathogenesis of sporadic PA. The majority of PA are characterized by mutations in the MEN1 tumor suppressor gene located on chromosome 11q which is identified in 25% to 40% of cases 16,18,74,83 . MEN1 gene alterations are characterized predominantly by loss of heterozygosity with biallelic inactivation.…”
Section: Genetics Of Parathyroid Neoplasiamentioning
confidence: 99%
“…In one study utilizing whole-exome sequencing, a low frequency of EZH2 mutations were identified 89. Additional alterations include aberrant methylation of promoters of WT1 , APC , RASSF1A , SFRP1 , SFRP2 , and SFRP4 , although these have not been firmly established as drivers of tumorigenesis 16,83,90…”
Section: Genetics Of Parathyroid Neoplasiamentioning
confidence: 99%
See 1 more Smart Citation
“…Genetic and epigenetic changes drive the development of parathyroid neoplasms [23][24][25] and influence the proteome. To assess the presence and cellular location of certain proteins, immunohistochemistry is an indispensable tool.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the mutational status of APC, RB, E-cadherin, MDM2 and p53 overexpression are considered useful biomarkers for parathyroid carcinomas’ diagnosis ( 7 ). Nevertheless, some PCas have an indolent growth and mimic benign lesions making their diagnosis more challenging ( 8 ). This clinical scenario is further complicated by the absence of accurate molecular markers supporting the differential diagnosis between parathyroid adenomas and carcinomas.…”
Section: Introductionmentioning
confidence: 99%